2019
DOI: 10.1071/an17849
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of improved extension services on awareness, knowledge, adoption rates and perceived benefits of smallholder dairy farmers in Pakistan

Abstract: The provision of effective extension services to smallholder farmers across both developing and developed countries remains a challenge worldwide. The objective of the study is to demonstrate the impacts of improved extension services on awareness, knowledge, adoption rates and perceived benefits of smallholder dairy farmers in Pakistan. An extension program was developed and implemented in five districts of Punjab (Okara, Pakpattan, Jhelum, Kasur and Bhakkar) and two districts of Sindh (Thatta and Badin) prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Recently, Wynn et al (40) reported that the current extension services in Pakistan cover only 40% of small-scale farmers, a majority of which are men who have a minimal role in day-to-day livestock activities and thus lead to poor adoption of extension messages. This is supported by Warriach et al (17) who implemented the whole-family approach (by involving men, women and children) for the extension program in Pakistan and found higher adoption rates leading to better animal health and on-farm benefits. Therefore, a whole-family approach for extension services might be a better approach to educate smallscale dairy farmers about health and production constraints for their animals.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, Wynn et al (40) reported that the current extension services in Pakistan cover only 40% of small-scale farmers, a majority of which are men who have a minimal role in day-to-day livestock activities and thus lead to poor adoption of extension messages. This is supported by Warriach et al (17) who implemented the whole-family approach (by involving men, women and children) for the extension program in Pakistan and found higher adoption rates leading to better animal health and on-farm benefits. Therefore, a whole-family approach for extension services might be a better approach to educate smallscale dairy farmers about health and production constraints for their animals.…”
Section: Discussionmentioning
confidence: 84%
“…The productivity of the Pakistani dairy sector is affected by constraints including nutrition, husbandry and health as well as limited access to vaccines and veterinary extension services (16,17). The major bovine diseases/syndromes reported from Pakistan include mastitis, foot-and-mouth disease (FMD), hemorrhagic septicemia, blackleg (or black quarter) caused by Clostridium chauvoei, internal and external parasitic diseases and hemoglobinuria (14,16,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…These positive results of CAAIT are likely to form a perception of benefits in holders' minds. Holders will compare the perceived benefits with their expectations and evaluate the value of CAAIT [30]. As a new and effective technology, the perception of the benefits of artificial intelligence technology generally shows a positive trend for holders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, smallholder dairy farmers in Africa have experience in rearing animals, but they are continuing to rely on traditional husbandry practices on their exotic-cross cows, such as using bulls instead of AI for reproduction, feeding poor quality diets, and keeping non-pregnant cows on the farm as long as they produce milk, which are likely contributing to low milk productivity and reproduction (Vaarst et al, 2007). In a study that included farmer training methods in Pakistan, substantial adoption rates of new techniques by the smallholder dairy farmers and their families were observed (Warriach et al, 2018). In that study, farmers who adopted the recommendations observed a wide range of positive impacts, including improved reproductive parameters.…”
Section: Factors Associated With Hazard Of Conceptionmentioning
confidence: 99%